The Power of Things: The Material Turn in Neo-Victorianism (KULT_online, 2024)
Neo-Victorian Things offers material readings of popular neo-Victorian multimedia that broaden the concept of neo-Victorianism and provide new insights into our contemporary fascination with the Victorian past. Each essay in the edited volume favors a particular ‘thing’ studied through the emerging strands of material culture. The book demonstrates that the things that appear in neo-Victorian multimedia play a central role in the revival of Victorian culture, identity and history. The volume makes a timely contribution to the field by critically examining ordinary objects, from a teapot to a haunted house.